2016
DOI: 10.1080/13574809.2016.1187558
|View full text |Cite
|
Sign up to set email alerts
|

Desert New Urbanism: testing for comfort in downtown Tempe, Arizona

Abstract: school of geographical sciences and urban Planning, arizona state university, Tempe, aZ, usa ABSTRACT Outdoor human comfort is determined for the remodelled downtown of Tempe, Arizona, USA, an acclaimed example of New Urbanist infill. The authors desired to know whether changes were accompanied by more comfortable conditions, especially in hot, dry summer months. The physiological equivalent temperature provided an assessment of year-round outdoor human comfort. Building compactness and tree shade that became … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
1
5
0
1
Order By: Relevance
“…Nighttime heat retention under shade structures and longwave radiation trapping in urban canyons create a trade-off between daytime and nighttime heat mitigation that should be investigated further. Middel et al (2016) did not find a difference in subjective thermal sensation votes under trees and photovoltaic canopy shade, indicating that the shade performance variation sensed by human-biometeorological instruments does not necessarily lead to perceived thermal comfort differences. More research is needed to translate ∆T MRT for each shade type into thermal comfort perceptions using field surveys and measurements.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Nighttime heat retention under shade structures and longwave radiation trapping in urban canyons create a trade-off between daytime and nighttime heat mitigation that should be investigated further. Middel et al (2016) did not find a difference in subjective thermal sensation votes under trees and photovoltaic canopy shade, indicating that the shade performance variation sensed by human-biometeorological instruments does not necessarily lead to perceived thermal comfort differences. More research is needed to translate ∆T MRT for each shade type into thermal comfort perceptions using field surveys and measurements.…”
Section: Discussionmentioning
confidence: 76%
“…In this context, urban greening has emerged as an investment priority for municipalities to combat adverse effects of climate change and improve urban sustainability, human health, and quality of life (Norton et al 2015). Trees cool the urban ecosystem through evapotranspiration and yield substantial thermal comfort benefits by providing shade (Bowler et al 2010;Armson et al 2013;Middel et al 2016). Past studies have shown that trees significantly impact the radiative heat exchange between the human body and the environment by attenuating the amount of direct solar radiation that increases the body's heat load and UV exposure (Aminipouri et al 2019;Downs et al 2019;Kántor et al 2016;Parisi et al 2019).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has a direct relationship with human comfort [218]. Crewe et al [219] employed SVF, estimated using photographs via RayMan program, in developing a relation for the PET, for the urban site in Tempe, AZ.…”
Section: Urban Heatmentioning
confidence: 99%
“…La intensidad de este proceso también ha llevado consigo controversias y mala praxis (Baños, 2016;Zambon et al, 2018). De manera general, el incremento de la superficie urbano-residencial se ha basado en la urbanización extensiva con la presencia de nuevas naturalezas urbanas (Llausàs et al, 2018), es decir, áreas urbanas caracterizadas por un modelo de baja densidad conocido en el ámbito anglosajón como "urban sprawl" donde es característica la presencia de espacios ajardinados privados y piscinas unifamiliares (Crewe et al, 2016;Morote & Hernández, 2016a). En las zonas costeras, especialmente del mediterráneo europeo, el desarrollo de la urbanización de baja densidad caracteriza a amplios espacios como, por ejemplo, la Costa Azul francesa (Fernández y Barrado, 2011) o en España (Romero et al, 2017).…”
unclassified